Penerapan Sistem Monitoring Hidroponik berbasis Internet of Things (IoT) - Imam Fathurrahman; Muhammad Saiful; L M Samsu (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Hydroponics is a method of planting without using soil media by utilizing water. The problem occurs when the farmer cannot control the water used in hydroponic. Therefore, we need a system to monitor the amount of water used in the hydroponic planting system. This service activity aims to develop and implement a hydroponic monitoring system based on IoT. This activity was carried out by students, followed by several accompanying lecturers. It aims to assist partners in measuring water content, temperature, and water pH in hydroponic plants. One of the business unit partners for this activity is SMEs engaged in hydroponic agricultural cultivation at the Science Technology & Industrial Park (STIPARK) NTB. This community service activity was held for four months. From the process of analyzing partner problems, they were testing the STIPARK management and hydroponic SME business partners and the community who later needed a hydroponic monitoring system based on the Internet of Things so that information could be received in real-time. This product can help hydroponic SME business partners know the level of water levels or nutrients, monitoring water temperature and water pH to help farmers increase crop yields from hydroponic cultivation